Divergent selection for shape of growth curve in Japanese quail. 6. Hatching time, hatchability and embryo mortality - Hyánková, L; Starosta, F (British poultry science, 2012)
1. Hatching time, hatchability of fertile eggs and embryo mortality under standard egg storage (1 or 5 days at 12 ± 1°C and 55% relative humidity) and incubation conditions (37.5 ± 0.2°C and 50% relative humidity) were analysed in lines long-term selected for high (HG) and low (LG) relative weight gain between 11 and 28 d of age, respectively, and constant body weight at 49 d of age. 2. Egg storage duration did not have an effect on average hatching time. LG quail, characterised by a fast postnatal growth rate immediately after hatching, hatched earlier than HG quail with a low early growth rate (about 391 vs. 406 h after egg setting, respectively). 3. In contrast to hatching time, the hatchability of fertile eggs was influenced by line as well as egg storage duration. Extended storage decreased hatching success in both lines. However, LG eggs exhibited a higher hatchability than HG eggs (1 d storage: 96.0 vs. 82.5%; 5 d storage: 88.7 vs. 72.7%, respectively). 4. Lower hatchability resulted mostly from a higher frequency of embryo death during early (up to d 7) and late (d 14 and later) phases of incubation. 5. An inadequate nutrient supply to embryos in consequence of developmental delay seems to be a key factor decreasing viability of embryos during incubation.
Keywords: selekce (genetika); Ovum; Animals; hnízdění; oviparie; Nesting Behavior; Coturnix; Time Factors; Oviparity; ovum; časové faktory; Male; zvířata; mužské pohlaví; Selection, Genetic; ženské pohlaví; Female